Assessment Of Physico-Chemical Parameters And Water Quality In Amlai Lake, Modasa Taluka, Gujarat, India (International Journal of Environmental Sciences, 2025)
Water quality assessment is crucial for effective management of aquatic ecosystems, especially in developing nations like India, where water bodies face increasing pollution loads from anthropogenic activities, industrial effluents, and domestic sewage. This study focuses on the determination and interpretation of physico-chemical parameters of water and soil samples from Amlai Lake, a significant wetland in Modasa Taluka, Gujarat, India. Data collected across winter, summer, and monsoon seasons in 2022 and 2023 for parameters such as temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), hardness, chlorides, alkalinity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), phosphate, and sulphate in water, and pH, total hardness, EC, calcium, magnesium, chloride, sulphate, sodium, potassium, and phosphate in soil, were analysed. The results for Amlai Lake revealed critically high BOD and COD levels in water, indicative of severe organic pollution, and low DO, threatening aquatic life. Soil analysis showed consistent alkalinity and seasonal variations in nutrient and mineral concentrations. This integrated approach highlights the localized impacts of pollutants and emphasizes the urgent need for targeted water quality management and eco-remediation measures for the sustainable health of Amlai Lake.